Cohort profile: the South African National Health Laboratory Service (NHLS) National HIV Cohort. Issue 10 (19th October 2022) - MacLeod, William B; Bor, Jacob; Candy, Sue; Maskew, Mhairi; Fox, Matthew P; Bulekova, Katia; Brennan, Alana T; Potter, James; Nattey, Cornelius; Onoya, Dorina; Mlisana, Koleka; Stevens, Wendy; et al.
Abstract : Purpose: South Africa's National Health Laboratory Service (NHLS) National HIV Cohort was established in 2015 to facilitate monitoring, evaluation and research on South Africa's National HIV Treatment Programme. In South Africa, 84.8% of people living with HIV know their HIV status; 70.7% who know their status are on ART; and 87.4% on ART are virologically suppressed. Participants: The NHLS National HIV Cohort includes the laboratory data of nearly all patients receiving HIV care in the public sector since April 2004. Patients are included in the cohort if they have received a CD4 count or HIV RNA viral load (VL) test. Using an anonymised unique patient identifier that we have developed and validated to linked test results, we observe patients prospectively through their laboratory results as they receive HIV care and treatment. Patients in HIV care are seen for laboratory monitoring every 6–12 months. Data collected include age, sex, facility location and test results for CD4 counts, VLs and laboratory tests used to screen for potential treatment complications. Findings to date: From April 2004 to April 2018, 63 million CD4 count and VL tests were conducted at 5483 facilities. 12.6 million unique patients had at least one CD4 count or VL, indicating they had accessed HIV care, and 7.1 million patients had a VL test indicating they had started antiretroviral therapy. The creation of NHLS National HIV Cohort has enabled longitudinal research on all lab-monitored patients in South Africa's national HIV programme, including analyses of (1) patient health at presentation; (2) care outcomes such as 'CD4 recovery', 'retention in care' and 'viral resuppression'; (3) patterns of transfer and re-entry into care; (4) facility-level variation in care outcomes; and (5) impacts of policies and guideline changes. Future plans: Continuous updating of the cohort, integration with available clinical data, and expansion to include tuberculosis and other lab-monitored comorbidities.